Workshop develops draft policy and guidelines for exotic fish strains in Ghana’s aquaculture sector - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Ghana’s rapidly growing aquaculture production has made the country the second-largest tilapia producer in Africa. Several factors account for this growth—including the introduction of the improved Akosombo strain, government interventions, new local feed production companies, and increasing local demand—but the main driver is the establishment of large-scale commercial cage production on Lake Volta.